Does the "Root Removal First" strategy prevent postoperative complications in the surgical removal of impacted mandibular third molars in the Pell and Gregory class C and horizontal position? - a randomized clinical trial - Bing Wang; Rui Sun; Tingting Li; Yuqi Sun; Linwei Zheng; Jihong Zhao (BMC, 2023)
Abstract Objective To evaluate the clinical outcomes of the "Root Removal First" strategy in the surgical removal of impacted mandibular third molar (IMTM) in the class C and horizontal position. Materials and methods A total of 274 cases were finally included in the statistics. The positions of IMTM in the horizontal position were confirmed by cone-beam computed tomography (CBCT). Cases were randomly divided into two groups: the "Root Removal First" strategy was applied in the new method (NM) group, and the conventional "Crown Removal First" strategy was executed in the traditional method (TM) group. The clinical information and relevant data upon follow-up were recorded. Results The duration of the surgical removal and the incidence rates of lower lip paresthesia in the NM group were significantly lower than those in the TM group. The degree of mobility of the adjacent mandibular second molar (M2) in the NM group was significantly lower than that in the TM group at 30 days and 3 months post-operation. The distal and buccal probing depth of the M2, as well as the exposed root length of M2 in the NM group, were significantly lower than those in the TM group 3 months post-operation. Conclusions The "Root Removal First" strategy can reduce the incidence rate of inferior alveolar nerve injury and periodontal complications of the M2 in the surgical removal of IMTM in class C and horizontal position with high efficiency. Trial registration ChiCTR2000040063.